INVESTIGATION ON THE POTENTIAL OF EUCALYPTUS CAMALDULENSIS WOOD IN PARTICLEBOARD INDUSTRY - Reza Hajihassani; Abdolrahman Hosseinzadeh; Amir Nourbakhsh; Abolfazl Kargarfard; Fardad Golbabaei (تحقیقات علوم چوب و کاغذ ایران, 2000)
In this investigation Eucalyptus camaldulensis wood for particle -board production and determinating physical and mechanical properties of boards have been studied. Variable factors such as resin content in three levels (9, 10 and 11 percent) and press time in three levels (5, 6 and 7 minutes) were investigated.Other factors such as resin type, hardner type, closing press time, mat moisture, board density and etc. were assumed constant. Three boards were produced for each combination of variables. Based on the DIN-68763 standard physical and mechanical properties including Modulus of Rupture (MGR), Modulus of Elastisity (MOE), Internal Bonding (IB) and thickness swelling (TS2 and TS24) after 2 and 24 hours immersion in water were tested.Based on the factorial experimental design at completely random block test data was analysis. The rcsuHs showed that polymerization of resin could be better at the amount of 11 percent resin content and 7 minutes of press time for partideboard production from Eucalyptus camaldulensis wood.